GAMBARAN TINGKAT KEPERCAYAAN DIRI MAHASISWA KEPERAWATAN YANG MENJALANI METODE PEMBELAJARAN TEKNIK SEVEN JUMP - Tiara Suci Iswandhie; Veny Elita; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
One of learning method in Faculty of Nursing University of Riau that focus to improved argument’s skill about some problems in little group discussion called Seven Jump technique. In discussion, students were required to give an opinion on some problems. Advantage of this discussion was to improved self-confidence of students. The aimed of this research was to identify the description of student’s self confidence level in learning method with Seven Jump technique. This research was conducted at Faculty of Nursing University of Riau during May – June 2018 by using simple descriptive method. Sample selection method used in this research was proportionate stratified random sampling with a total of samples were 209 respondents. Data collection was done by using questionnaires and data processing was done by computerization process which was displayed in the form of frequency distribution and percentage. The results was showed that Nursing Faculty’s student in Riau University had high self-confidence. It was suggested to Nursing Faculty’s students in University of Riau to maintain and improved self-confidence of students then the students can get good self-confidence in academic.Keywords: nursing students, self-confidence, seven jump